(untitled) (Global Journal of Medical Research, 2024)
This study aims to explore the green technology strategies for the preparation of fluoxetine through the research on the greenization of catalysts and membrane treatment of wastewater The study show that green technology strategies can effectively reduce the environmental pollution and resource consumption during the preparation of fluoxetine At the same time the integration and prospects of green technology strategies were analyzed and its potential value and broad application prospects were provided in the preparation of fluoxetine This research is of great significance for promoting the development of fluoxetine preparation processes towards a green environmentally friendly high efficiency and sustainable development